THE EFFECTIVENESS OF TAHFIZ LEARNING IN ACEH BESAR REGENCY - Fithriani Fithriani (Edukasi Islami : Jurnal Pendidikan Islam, 2022)
The Quran is one of Allah's miracles revealed to the Prophet Muhammad SAW, in which its authenticity is maintained until the end of time. One way to maintain the Quran’s purity is to memorize it. Recently, the interest in memorizing the Quran has been significantly high among children and adults, evidenced by the establishment of tahfiz (Quran memorizing) institutions by the government, society, and private educational institutions. The high interest in memorizing the Quran is a form of God's guidance to maintain the purity of His words. Parents have a significant role in determining their children’s interest in memorizing the Quran. This unique phenomenon occurred in Aceh Besar Regency, the provincial capital and the busiest city in Aceh province. While busy with their career and roles as household heads or homemakers, Aceh Besar parents have successfully made their children hafiz and hafizah (Quran memorizers). This condition is undoubtedly interesting to be studied. This qualitative research observed four hafiz families in Aceh Besar Regency. The data were collected via observation and interviews. The result indicates that Aceh Besar families used talaqqī,  tasmī’, tikrāri, and muraja'ah as tahfiz learning methods, while they used individual (ifrādi), tsawāb wa iqāb, and uswah, as the techniques. It is concluded that the effective tahfiz learning model applied in Aceh Besar families is the طريقة تكاملية  (integrated method).